APPLICATION FRII AT FASHION NIGHT INSPIRATION SRIKANDI - Yolanda Jatmika (Canthing, 2014)
Designing fashion final project aims to design evening dress mature women with a source of ideas Heroine puppet figure with fashion style women's clothing and Java applications with additional Friil sequins and embroidery as an innovation. Its main ingredient is silk batik motif in Parang Klithik combined with velvet cloth. The use of batik motif Klithik Parang aims to preserve and maintain the culture of Indonesia classical motifs.Batik is the traditional process of writing to the process pencantingan to pelorotan night. While silk and velvet clothing can look attractive with a shiny fabric effects, and modern fashions. The results of making clothes Evening consists of three fashion, Fashion Model I with two pieces dress consists of a red color combination of maroon and dark green. Clothing Model II with two pices dress color combination of red and dark brown two pieces and the pieces used in the form of one maroon red and purple. As well as taking the soul Heroine impressed gallant but still feminine.